RESEARCH OF INFLUENCE OF MODERN INFORMATION TECHNOLOGIES ON THE WORK EFFICIENCY INCREASE OF O&G ENTERPRISES - Kochkodan, V. B. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
In the article the influence of modern information technologies on the enterprises work efficiency increase in the oil and gas sector is investigated. Methods of comparison, synthesis and situational analysis are used for the research. Studies conducted in 2017 show that worldwide oil and gas companies consider faster and better way of the decision-making process as the top advantage of digitalisation. It has been established that digitalisation projects are recognized as a key component of in the operating strategy of companies in the oil and gas complex. Oil and gas companies can implement both operational and strategic digitalisation. Operational digitalisation is action-oriented, practical and delivers immediate benefit, it allows oil and gas companies to get easily access to certain data arrays, combine them, make generalizations, establish relationships and accurately predict the effects. The advantages of operational digitalisation are: relatively small investments, gradual deployment, reduction of equipment downtime, and reduction of operating costs. Strategic digitalisation is a long-term structural approach that focuses on changing the design, construction and operation of wells and deposits in general. Six stages of the operational digitalisation program of oil and gas companies are identified: evaluation of assets and operations in order to find weak links that are needed to be improved; identification of value factors and the magnitude of the possible influence on them; evaluation of the digitalisation maturity; selection of measures that best balance the benefits and risks of implementation; implementation of selected measures; evaluation of the results. The experience of digital technologies implementation in Lundin Petroleum was reviewed. It has been revealed that the key to digitalisation were company operations, not information technologies. In general, digital technologies allow oil and gas companies to reach a higher level of efficiency, reduce unproductive time losses, reduce downtime, increase the efficiency of management activities, take better care of the environment, etc.